(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Acne has a multifactorial and complex etiology making therapies a challenge. Multimodality approach with oral topical retinoid and hormonal therapies constitutes the main framework of treating acne. Partial remission, incompliance, and adverse effects of medical therapies often increase demands of safe and fast therapies, especially, interventional therapies for acne. Interventional procedures comprising chemical peels and laser and light based devices constitute adjunctive treatments for acne and have gained some importance in the recent years.